1005 Reducing ed revisits among copd patients managed in ed observation unit: reliable implementation of copd care-bundle using improvement science. (21st November 2017) - Zafar, Muhammad; Loftus, Timothy; Palmer, Jack; Phillips, Michael; Ko, Jonathan; Ward, Steven; Mueller, Eric; Dalhover, Amber; Alessandrini, Evaline
Abstract : Background: COPD exacerbations (eCOPD) deleteriously effects patient outcomes and healthcare spending. Emergency Department observation units (ED-Obs) provide short-term acute care in order to reduce resource utilisation, however successful COPD-specific programs in ED-Obs are lacking. Objectives: Achieve 90% reliable implementation of COPD care-bundle among eCOPD patients discharged from ED-Obs by April 2017. The overall goal is to reduce 30 day all-cause ED revisits for eCOPD patients discharged from ED-Obs from the baseline rate of 49%. Methods: Setting: An 800-bed academic hospital with 700 eCOPD ED encounters/year, out of which 20% triage to ED-Obs. All patients triaged to ED-Obs with eCOPD diagnosis were included. A five-element COPD bundle designed to mitigate system-level failures, was adopted from in-patient setting. The bundle components were: appropriate inhaler regimen, 30 day inhaler supply, personalised inhaler education, standardised discharge instructions and follow-up in 15 days. A multidisciplinary team was formed to support bundle implementation within the 24 hours ED-Obs stay using Model for Improvement. Bundle component adherence and 30 day ED revisit rates were monitored using SPC p-charts. Hospitalisation rate from ED-Obs was used as balancing measure. Results: The patient characteristics were similar in baseline and post-bundle period. Multiple PDSA cycles were performed to achieve a final process (Figure 1). The adherence to COPD care bundle components has maintained >90% from 4/2017–8/2017 (Figure 2). The 30 day all-cause ED revisit rate reduced from 49% to 28% with a pending system-shift on SPC (Figure 3). Hospitalisation rate remained unchanged. Conclusions: Improving care at discharge transition of eCOPD patients from ED-Obs to home through reliable adherence to COPD care-bundle reduces 30 day all-cause ED revisits.